Heavy metal immobilization of contaminated soil by waste amendments / Mehrnaz Ashrafi - Ashrafi, Mehrnaz (2014)
Heavy metal-contaminated soil is one of the major environmental pollution issues all over the world. In this study four low-cost amendments, namely eggshell (inorganic), banana stem, potato peel and coconut husk (organic) were added to a slightly alkaline soil for the purpose of in situ immobilization of Pb, Cd, Zn and Cu, thus to modify their potential environmental impacts. The artificially metal-contaminated soil was treated with 5% inorganic amendment or 10% organic amendment for a period of 12 weeks. To simulate the rainfall conditions, a metal leaching experiment was designed and the total concentrations of the metals in the leachates were determined every two weeks by using ICP-OES. The results from the metal leaching analysis revealed that the eggshell amendment generally reduced the concentrations of Pb, Cd and Zn in the leachates, whereas the banana stem amendment was effective only on the reduction of Cd concentration in the leachates. The cumulative amount of Pb, Cd and Zn in the leachates after 6 leaching events was reduced by 14%, 83% and 70%, respectively in eggshell amended soil and the cumulative amount of Cd was reduced by 78% in banana stem amended soil. Both potato peel and coconut husk amendments did not have any positive effect on the metal leaching. A sequential extraction analysis was carried out on soils treated with eggshell and banana stem at the end of the experiment to find out the chemical speciation of the heavy metals. The findings from the sequential extraction analysis indicated that the addition of eggshell amendment notably decreased the mobility of Pb, Cd and Zn in the soil by transforming their readily available form to the less accessible fractions. The banana stem amendment also reduced exchangeable form of Cd and increased its residual form.